High yield and high purity metallicity-based separation methods for single walled carbon nanotubes - Sara Mesgari Hagh (Nanyang Technological University, 2014)
The unique electronic, mechanical and thermal properties of single-walled carbon nanotubes (SWNTs) make them potentially suitable for many applications in electronics, optics and other areas of materials science. However, all state-of-the-art SWNT synthesis methods produce mixtures containing both metallic and semiconducting nanotube species and such mixtures are unsuitable for many electronic applications. Therefore, a great deal of attention has been paid to post-synthesis separation of metallic from semiconducting nanotubes. Many metallicity-based SWNTs separation techniques have been reported and these include chromatography, density-gradient ultracentrifugation and selective chemistry using biomolecules, amines or aromatic molecules. However, these methods have a number of well-known drawbacks including low process yield, low purity and/or degradation of the original properties of SWNTs. A scalable method for high purity cum high yield separation of metallic from semiconducting SWNTs is highly appealing and remains a worldwide challenge. To achieve the latter, the focus of this study was placed on improving the selectivity and yield of gel electrophoresis and selective chemistry methods. Due to their potential high yield, simplicity and scalability, these technologies were identified as potential candidates for developing high yield cum high purity separation methods. However, both gel electrophoresis and selective chemistry methods have a number of drawbacks. The drawbacks of agarose gel electrophoresis include the insufficient purity of the separated semiconducting nanotubes achieved and the difficulties in removal of the gel surrounding the nanotubes after AGE to achieve clean semiconducting nanotubes for use in electronics. In addition, the drawbacks of state-of-the-art selective chemistry include the relatively lower selectivity for large diameter nanotubes and the aggressive nature of available chemistries. In the present work, a comprehensive experimental study was conducted to improve the efficiency of AGE and selective chemistry techniques with the objective of developing scalable and efficient methods for separation of metallic from semiconducting nanotubes. Three novel techniques were developed. Firstly, we found that excellent separation with AGE can be achieved using chondroitin sulfate (CS-A), a novel polymer-based surfactant. The purity and process yield achieved using our proposed CS-A/AGE method were 93% (compared to 85% achievable using state-of-the-art SDS-assisted AGE) and 25%, respectively. Secondly, we developed a high yield cum high purity method based on selective chemistry using a novel doubly selective sulfonate-functionalized naphthalene-based azo compound that can achieve highly pure, >93% semiconducting, nanotubes with high yield (up to 41%) when followed by centrifugation. Thirdly, we developed a combined selective chemistry-assisted agarose gel electrophoresis (AGE) technique to produce highly purified semiconducting nanotubes (98%) purity with a considerably high process yield (~18%). The efficiency of the above techniques was verified by extensive characterization. In addition, we developed a chlorosulfonic acid (HSO3Cl) treatment technique that can be used to effectively remove the agarose gel and the dispersing agent after AGE to achieve clean semiconducting nanotubes suitable for electronic applications. We applied the purified nanotubes in field effect transistors to examine the suitability of our purified nanotubes for the electronic applications.